Short-Term Radiographic Outcome After Distal Chevron Osteotomy for Hallux Valgus Using Intramedullary Plates With an Amended Algorithm for the Surgical Management of Hallux Valgus. Issue 1 (February 2019) - Matsumoto, Takumi; Gross, Christopher E.; Parekh, Selene G.
Distal Chevron osteotomy is a well-established surgical procedure for mild to moderate hallux valgus deformity. Many methods have been described for fixation of osteotomy site; secure fixation, enabling large displacement of the metatarsal head, is one of the essentials of this procedure. The purpose of the present study was to evaluate the short-term radiographic outcome of a distal Chevron osteotomy using an intramedullary plate for the correction of hallux valgus deformity. The present study evaluated 37 patients (40 feet) who underwent distal Chevron osteotomy using an intramedullary plate by periodic radiographs obtained preoperatively and at 4 weeks, 8 weeks, 3 months, and 6 months postoperatively. Correction of the hallux valgus angle averaged 17.8°, intermetatarsal angle 7.4°, distal metatarsal articular angle 2.7°, and sesamoid position 1.4 stages at 3 months postoperatively. The average lateral shift of the capital fragment was 6.5 mm. All patients achieved bone union, and there were no cases of dislocation, displacement, or avascular necrosis of the metatarsal head fragment. In conclusion, a distal Chevron osteotomy using an intramedullary plate was a favorable method for the correction of mild to moderate hallux valgus deformity. Levels of Evidence: Level IV: Case series